GLP-1 Receptor Agonists in Diabetic Kidney Disease: From Clinical Outcomes to Mechanisms - Kawanami, Daiji; Takashi, Yuichi (Frontiers in Pharmacology, 2020)
Diabetic Kidney Disease (DKD) is the leading cause of end stage renal disease (ESRD) worldwide. DKD has been implicated as a risk factor for cardiovascular disease (CVD). Glucagon-like peptide 1 receptor agonists (GLP-1RAs) are now widely used in the treatment of patients with type 2 diabetes (T2D). A series of clinical and experimental studies demonstrated that GLP-1RAs have beneficial effects on diabetic kidney disease, independent of their glucose-lowering abilities, which are mediated by natriuresis, anti-inflammatory and anti-oxidative stress properties. Recent clinical trials have demonstrated that GLP-1RAs have beneficial effects on renal outcomes, especially in patients with T2D who are at high risk for CVD. These findings suggest that GLP-1RAs hold great promise in preventing the onset and progression of DKD. In this review article, we highlight the current understanding of the clinical efficacy and the mechanisms underlying the effects of GLP-1RAs in DKD.